2014
DOI: 10.3748/wjg.v20.i10.2681
|View full text |Cite
|
Sign up to set email alerts
|

Forward-viewing radial-array echoendoscope for staging of colon cancer beyond the rectum

Abstract: The echoendoscope is a feasible staging tool for colon cancer beyond rectum. However, accuracy of the echoendoscope needs to be verified by larger systematic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It is reasonable to believe that these applications could also be used for EUS in the colon. A recent study emphasizes the feasibility of forward-viewing radial-array EUS of staging colonic cancers in all segments of the colon [9] and we tend to carefully agree, based on our own results for Blow risk^tu-mours, especially for T-stages.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is reasonable to believe that these applications could also be used for EUS in the colon. A recent study emphasizes the feasibility of forward-viewing radial-array EUS of staging colonic cancers in all segments of the colon [9] and we tend to carefully agree, based on our own results for Blow risk^tu-mours, especially for T-stages.…”
Section: Discussionmentioning
confidence: 68%
“…MRI has been evaluated in a few papers with varying results [4,8]. Only limited literature exists concerning endoscopic ultrasonography (EUS) for staging of colonic cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, only six were relevant. [ 12 13 14 15 16 17 ] A flow chart of the search strategy is presented in Figure 1 . Six potential studies were excluded from the study due to data on colonic cancers alone could not be provided.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] None of the studies reported any complication due to the diagnostic procedures either with miniprobes[ 12 16 17 ] or with radial transducers. [ 13 14 15 ] Some, however, had to give up tumor staging due to technical difficulties; these were not included in our analysis. [ 12 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…Prospective radial array echogenic endoscopy can be used to diagnose colon cancer, but it has been concluded that this method is not suitable for locally advanced colon cancer, nor is it suitable for assessing peripheral lesions of colon cancer, and its accuracy also needs to be expanded to continue research [31]. Further research has found many diagnostic markers.…”
Section: Diagnosismentioning
confidence: 99%